Implementation of Digital-Based Marketing Strategies to Increase Promotion Effectiveness in Integrated Islamic Elementary Schools - Santi Setiawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This research aims to evaluate the implementation of digital-based marketing strategies in enhancing promotional effectiveness at AN-NAHAR Integrated Islamic Elementary School (SDIT) in Pangandaran. The background of this study stems from the need for educational institutions to adapt to developments in communication technology, as well as to improve the positive image of the school in attracting new students. Conventional promotional strategies are considered less relevant in the digital era, thus social media-based approaches and digital platforms become a more effective alternative. The research method used is qualitative with a case study approach. Data collection techniques include observation, in-depth interviews, documentation, and literature study. The subjects of the research consist of the school principal, the social media team, teachers, students, parents, and the surrounding community. Data analysis is conducted through data reduction, data presentation, and drawing conclusions, with validation using source and technique triangulation. The research results indicate that digital marketing strategies through Instagram, TikTok, YouTube, Facebook, and WhatsApp have successfully increased the visibility of the school, built a positive image, and encouraged an increase in the number of students. The main supporting factors include content adaptation to social media trends, active interaction with parents through digital channels, and collaboration with the local community. Meanwhile, the inhibiting factors include the school's website not being optimal, limited human resources, and competition among educational institutions. The conclusion of this study emphasizes that digital marketing is not just a promotional tool, but a communication strategy that builds emotional connections and public trust. SDIT AN-NAHAR Pangandaran has demonstrated that this approach can be effectively applied in the context of integrated Islamic education, while upholding the values of ethics, transparency, and social benefit